Análisis de las aplicaciones móviles de los medios de comunicación de la ciudad de Loja, para la difusión de la información, año 2017-2018 - Acevedo Rengel, Jordy Bryan (2019)
The present work was elaborated and developed with the objective of carrying out a detailed and updated study of the analysis of the mobile applications of the media of the city of Loja, for the diffusion of information. To know the handling of information, to identify the advantages and disadvantages of opting for this new means of mobile applications technology. The investigation was carried out in the period between 2017 - 2018, taking as subjects to investigate, the mobile applications of the media of greater audience of the city of Loja. In this work we used the scientific method that served to contextualize the research, through observation, analysis and reasoning; deductive method that served to analyze the main problem of the creation of applications in the media of the city of Loja; analytical method that allowed to study details, needs, behaviors, opinions and characteristics of the relevant information of the research; statistical method that allowed to order, process and interpret the information gathered in the field of study; descriptive method we were able to deepen and describe fundamental aspects that allowed us to process the field information, conclusions and final recommendations. In addition, techniques were used such as surveys of Loja citizens, interviews with directors of the media, graduates of systems in programming and observation of the media with the completion of fact sheets that contributed to this work. Finally, a mobile application was designed as a proposal for the integral digital medium of the Social Communication Career at the National University of Loja.